Penyebab Sulitnya Siswa Menjawab Soal HOTS dalam Pembelajaran Sosiologi di Kelas XI IPS SMAN 1 Batang Kapas Pesisir Selatan - Dalman, Rizki Pratama; Junaidi, Junaidi (Universitas Negeri Padang, 2022)
This article was written to find out the cause of the difficulty of students answering the HOTS questions in learning sociology in class XI IPS at SMAN 1 Batang Kapas, Pesisir Selatan. This type of research uses qualitative methods with the type of case study research. The criteria for informants in this study were students of class XI IPS and sociology teachers in class XI IPS at SMAN 1 Batang Kapas. The informant selection technique in this study used purposive sampling. This study discusses that, the cause of the difficulty of students answering HOTS questions is caused by (1) Students Do not Understand the Material. Interviews with several students obtained information that they did not understand the material because of the difficulty of the teacher's teaching method, either because the teacher was difficult to understand, the delivery of the material was not good or the teacher was too quick to teach the material in the learning process. Another thing based on observations can be found the cause of difficulty understanding the material because they are not serious in learning. This can be seen from the attitude of those who watch while studying and some are related to other students. Students' disinterest in learning is caused by teachers who teach a lot using the lecture method so that students become bored and students' thinking skills are not honed. The cause of teachers who use the lecture method a lot is due to the lack of training that can be related to HOTS learning and about HOTS, so that the experience of teachers about HOTS is still relatively low and (2) Students Do not Understand Question Commands. Based on interviews, information was obtained that the reason why students did not understand the instructions about their reasons was never discussed by the teacher about what HOTS questions were and what were the requirements for a HOTS question. This is permitted by the teacher where the teacher only gives HOTS questions to students, the HOTS questions given are also still few so that students are not used to it and do not only answer the HOTS questions that are tested on them. This happened because teachers did not receive training on HOTS, besides that the comprehension ability of class XI IPS students could be said to be still in the lower middle class, which was also confirmed by the Sociology teacher.